Enhancing Biogas Production through the Co-Digestion of Indigofera and Cow Manure for Electricity Generation - Suyitno, Suyitno; Juwana, Wibawa Endra; Muqoffa, Mohamad (Journal of Engineering and Technological Sciences, 2025)
The research examines the augmentation of biogas generation through the co-digestion of Indigofera tinctoria waste and cow manure, emphasising the optimization of parameters for enhanced efficiency. Anaerobic digestion presents potential for sustainable waste management and renewable energy generation. The initial discussion underscores the significance of Indigofera tinctoria, alongside challenges in managing agricultural and organic waste. The methodology encompasses substrate preparation, reactor design, and biogas utilization for electricity generation. Results indicate that substrate feeding rates and pH levels significantly influence biogas production, with optimal efficiency observed when pH is maintained between 6 and 7. Feeding rates are identified as a critical factor, highlighting the necessity for precise optimization. Additionally, managing hydrogen sulfide content is vital to mitigate corrosion risks, which can be addressed through adjustments to substrate composition. An interaction analysis between substrate feeding rates and pH revealed no significant combined effects, emphasizing the importance of understanding individual parameter dynamics to maximize production efficiency. Optimal load conditions were identified, with diminishing returns observed beyond a specific threshold. This study provides valuable insights into improving biogas production efficiency from Indigofera tinctoria waste and cow manure. Key recommendations include the optimization of substrate composition and stringent pH regulation to promote sustainable biogas production practices. Future research is encouraged to further refine biogas technology and advance its application in renewable energy systems.